Good Maya women : migration and revitalization of clothing and language in highland Guatemala - Bennett, Joyce N., 1985- (The University of Alabama Press, 2022)
"Analyzes the forced migration of Maya women from the highlands of Guatemala and their turn toward language and indigenous clothing revitalization upon their return home"--